The Full Returns to the Choice of Occupation and Education - Andrew E. Clark; Maria Cotofan; Richard Layard (Institute of Labor Economics (IZA), 2022)
Information on both earnings and non-pecuniary rewards is needed to understand the occupational dispersion of wellbeing. We analyse subjective wellbeing in a large UK sample to construct a measure of "full earnings", the sum of earnings and the value of non-pecuniary rewards, in 90 different occupations. Labour-market inequality is underestimated: the dispersion of full earnings is one-third larger than the dispersion of earnings. Equally, the gender and ethnic gaps in the labour market are larger than those in earnings alone, and the full returns to education on the labour market are underestimated. These results are similar in data on US workers. In neither cross-section nor panel data do we find evidence of compensating differentials.
Keywords: I31; J31; 330; occupation; wages; non-pecuniary benefits; inequality